Budgetary Policy in the Financial Security System - МЕLNYKV.; SAVASTEIEVAО. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
The financial security of the state becomes especially important given the crisis manifestations in the global financial system, loosening of the state control over the monetary system and the increasing political pressures on economic processes. The article’s objective is to review the theoretical foundations of the financial security and analyze the impact of the budgetary policy on the budgetary security as the core the financial security of the state. A statistical analysis of the budgetary policy impact on the budgetary security is made for the period of 2015–2019 on the basis of Methodological Recommendations on Computation of the Economic Security Level in Ukraine, with assessing four indicators: (i) the ratio of the public budget deficit/surplus to GDP; (ii) the share of deficit of budget and off-budget funds of the general government in GDP; (iii) the share of GDP redistributed via the consolidated budget; (iv) the ratio of cumulated payment for debt service and repayment to the public budget revenue. The assessment scale ranges from 0 to 1 (or from 0 to 100%) and consists of five intervals: absolutely critical level of danger; critical level of danger; dangerous level; unsatisfactory security level; satisfactory security level; optimal security level. Results of the analysis give grounds to suggest that the policy concerned with public borrowing, debt service and repayment is must be urgently revised, because the respective indicator (which is the ratio of cumulated payment for debt service and repayment to the public budget revenue) was signaling extremely high levels threats to the budgetary security in 2015–2019 and, eventually, to the financial security of the country.